DOI: 10.14264/uql.2017.924
|View full text |Cite
|
Sign up to set email alerts
|

Commercialisation of smallholder agriculture in Cambodia: impact of the cassava boom on rural livelihoods and agrarian change

Abstract: Agricultural commercialisation is a process that involves the transformation of subsistence-oriented smallholder farming systems into systems that are primarily oriented toward production for the market. Agricultural production is no longer viewed merely as the means to meet household consumption requirements, drawing on local resources, but becomes the household"s main incomegenerating activity, tying farmers into the wider market economy, not only through the sale of farm commodities, but through the purchas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 94 publications
(160 reference statements)
0
15
0
Order By: Relevance
“…Proximate (or direct) causes of land-use change constitute human activities or immediate actions that originate from intended land use and directly affect land cover, while underlying (or indirect, or root) driving forces are fundamental forces that underpin the more proximate causes of land-cover change (Lambin et al, 2003). Based on the literature review relevant to the agricultural expansion in the Northwest of Cambodia (Diepart & Dupuis, 2014;Diepart & Sem, 2015, 2018Montgomery et al, 2017;Touch, Martin, Scott, Cowie, & Liu, 2016, 2017, we identified three main categories of proximate causes: agricultural expansion and intensification, infrastructure development, and resources exploitation, and five main categories of underlying factors: political and institutional factors, economic factors, demographic factors, technological factors, and environmental factors (Fig. 1).…”
Section: Framing the Lucc Analysis: A Multi-scale Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximate (or direct) causes of land-use change constitute human activities or immediate actions that originate from intended land use and directly affect land cover, while underlying (or indirect, or root) driving forces are fundamental forces that underpin the more proximate causes of land-cover change (Lambin et al, 2003). Based on the literature review relevant to the agricultural expansion in the Northwest of Cambodia (Diepart & Dupuis, 2014;Diepart & Sem, 2015, 2018Montgomery et al, 2017;Touch, Martin, Scott, Cowie, & Liu, 2016, 2017, we identified three main categories of proximate causes: agricultural expansion and intensification, infrastructure development, and resources exploitation, and five main categories of underlying factors: political and institutional factors, economic factors, demographic factors, technological factors, and environmental factors (Fig. 1).…”
Section: Framing the Lucc Analysis: A Multi-scale Approachmentioning
confidence: 99%
“…A second body of knowledge examined the economics of boom crop production and the commercialization of smallholder agriculture. This literature argues that despite a quick increase in farm income and household assets in the early stages of the boom (Kem, 2017), agricultural expansion quickly made the farmers highly dependent on market fluctuations and generated negative impacts, including soil degradation and reductions in yield and crop profitability (Belfield, Martin, & Scott, 2013;Kong et al, 2016;Montgomery, Martin, Guppy, Wright, & Tighe, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most frequently reported impacts include narrowing of livelihood options, vulnerability to indebtedness, increased labor demand, declining supplies of staple food crops, a reduction in customary practices and sociocultural wellbeing and marginalization of certain groups [95]. Meanwhile, the increase in overall household income may offset the decline in food crop production, the loss of diverse economic activities poses a potential risk to livelihood security and leave the farmers vulnerable to fluctuating yields and prices [15,96].…”
Section: Socio-economic Impacts Of Annual and Perennial Cropsmentioning
confidence: 99%
“…Many smallholders relying on loans had to sell land because of limited capacity to cope with farm and household shocks. Hence the transition to intensive production of cassava resulted in growing inequality and contrasting livelihood trajectories [95].…”
Section: Socio-economic Impacts Of Annual and Perennial Cropsmentioning
confidence: 99%
“…This approach is based on the assumption that low agricultural productivity can primarily be solved through adoption of technical and market-based solutions (Scrinis and Lyons, 2010). Current agricultural policies across developing countries such as Ghana, position the processes of modernisation and commercialisation as crucial to stimulate the structural transformation of economies (IFPRI, 2009;Kem, 2017;Moseley, 2017;Sun, 2011). However, this view ignores the socio-cultural transformations such policy shifts engender, including erosion of indigenous knowledge, commercialisation of social and production relations, and marginalisation of poor farmers that is so often associated with the modernisation of agriculture (Bernstein, 1990;Francine, 1972;GRAIN, 2018;Shiva, 1993).…”
Section: List Of Figuresmentioning
confidence: 99%